Water and Beverages Intake Among Workers Amid the COVID-19 Pandemic in Indonesia - Sunardi, Diana; Chandra, Dian Novita; Medise, Bernie Endyarni; Manikam, Nurul Ratna Mutu; Friska, Dewi; Lestari, Wiji; Insani, Putri Novia Choiri (Frontiers in Nutrition, 2022)
As the Covid-19 pandemic hit worldwide in the early 2020, people were urged to alter their behavior to prevent disease spread, thus, led to change water intake. This study aimed to analyze water and beverage intake among health workers and general workers during Covid-19 pandemic in Indonesia. This study was a comparative descriptive study where the participants were 20 – 45 years old health workers and general workers in Indonesia. Data collected included demographic, water and beverage intake, physical activity, nutrient intake, and body weight and height. All data collection was obtained online using self-reported questionnaire. Water intake data was collected for 7 days consecutively using 7 days fluid record. There were 246 participants comprised of 102 (41.5%) general workers and 144 (58.5%) health workers who were analyzed in this study. All participants showed barely adequate intake of daily total fluid 1882 (1473 – 2433) mL/day. Total fluid intake of general workers was 1759 (1447 – 2396) mL/day, meanwhile health workers was slightly higher 1939 (1516 – 2446) mL/day (P-Value = 0.378). Among health workers who were highly exposed to Covid-19 patient showed the highest percentage in drinking water adequately (20 participants, 60.6% compared to health workers who worked under moderate (29 participants, 48.3%) and low (24 participants, 47.2%) level of exposure to Covid-19 patient. In conclusion, workers need to improve their daily fluid intake. This study also showed better behavior of water consumption among health worker compared to general worker despite of their strict personal protection equipment during working hour.